Pragmatic concerns fuel nuclear support. - Miller, S.
In recent years, nuclear power has undergone some resurgence of interest as its supporters have positioned it as a solution to air pollution, global warming, and energy shortages. Since 1999, the percentage of people responding favorably has ranged from 46 percent to 52 percent. One poll of California residents taken in May 2001 during the period of rolling blackouts even showed 59 percent supporting expanding nuclear power. Still, there is no clear public mandate for a significant buildup of new plants. The nuclear power industry is counting on this combination of energy shortages, fossil fuel pollution, and the promise of cheaper, more efficient technologies to tip the public's perception in its favor. This paper discusses public opinion regarding nuclear power in the US, Europe and Japan. The chances of new nuclear plants receiving public support appears higher now than it has been in recent decades. Still, the industry must address substantial public concerns about plant safety and waste disposal before any new initiative is widely accepted
Keywords: Europe; Japan; USA; Air pollution solution; Energy shortages solution; Fossil fuel pollution; Global warming solution; Nuclear power; Power plant safety; Public opinion; Waste disposal